2011
DOI: 10.1590/s0104-77602011000200011
|View full text |Cite
|
Sign up to set email alerts
|

Características colorimétricas entre as seções anatômicas da madeira de muirapiranga (Brosimum sp.)

Abstract: Objetivou-se, com este trabalho, avaliar as características colorimétricas das três seções anatômicas (transversal, tangencial e radial) da madeira de muirapiranga (Brosimum sp.), utilizando o sistema CIELAB 1976 (Comissão Internacional de Iluminantes). A partir de 10 amostras de madeira, obtidas em movelarias do município de Cruzeiro do Sul - AC, foram determinados os parâmetros colorimétricos: luminosidade (L*), coordenada do eixo vermelho-verde (a*), coordenada do eixo azul-amarelo (b*), saturação (C) e âng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 5 publications
2
9
0
5
Order By: Relevance
“…The lowest results tended to be presented in the transversal section in the samples of C. xanthocarpa, in the regions next to the pith and intermediate, in all samples of M. retorta, and in the intermediate region of P. peruviana. Atayde et al (2011) also observed it when characterizing the colorimetric parameters of the three sections of the wood of muirapiranga. As far as the regions of the disc are concerned, C. xanthocarpa and P. peruviana showed no significant statistical difference, such as the radial section of E. pyriformis.…”
Section: Factor Analysismentioning
confidence: 72%
See 1 more Smart Citation
“…The lowest results tended to be presented in the transversal section in the samples of C. xanthocarpa, in the regions next to the pith and intermediate, in all samples of M. retorta, and in the intermediate region of P. peruviana. Atayde et al (2011) also observed it when characterizing the colorimetric parameters of the three sections of the wood of muirapiranga. As far as the regions of the disc are concerned, C. xanthocarpa and P. peruviana showed no significant statistical difference, such as the radial section of E. pyriformis.…”
Section: Factor Analysismentioning
confidence: 72%
“…These characteristics are influenced by several factors, especially the variation among species, among each tree of the same species, and within the same tree (SILVA et al, 2017). In addition, variation may occur according to the anatomical section in which the analysis was performed (ATAYDE et al, 2011;NISHINO et al, 2000). Therefore, in order to minimize interferences in determining wood color, correct and accurate reading of the CIE L*a*b* system is indicated, which can be made using colorimeters or spectrophotometers (MORI et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The statistically similarity between axes differs from results observed in literature. Atayde et al (2011) observed different colors between tangential and radial sections of tropical wood Muirapiranga (Brosimum sp.). In that case, the only parameter statistically equal between sections was a*, but even then tangential cuts were more reddish than radial ones (with yellow tones) as b* values were higher in the radial axe than in the tangential.…”
Section: Resultsmentioning
confidence: 95%
“…As madeiras de Eucalyptus robusta e Eucalyptus saligna apresentaram os menores h ab , ou seja, maior proximidade do eixo vermelho, caracterizando a cor mais avermelhada dessas espécies (Tabela 1). Em madeiras com valores de a* > 10, a tonalidade vermelha manifesta-se de forma mais pronunciada que a amarela (b*), predominando a nuance vermelha na formação da cor (ATAYDE et al, 2011;COSTA et al, 2011;GONÇALEZ et al, 2001). Sendo assim, obtem-se dois grupos de madeiras em termo de cor: madeiras amareladas (Corymbia citriodora e Eucalyptus camaldulensis) e madeiras avermelhadas (Eucalyptus pellita, Eucalyptus robusta, Eucalyptus saligna, Eucalyptus urophylla e Eucalyptus grandis.…”
Section: Espéciesunclassified